CPX/D underestimates VO(2) in athletes compared with an automated Douglas bag system - Gore, C. J.; Clark, R. J.; Shipp, N. J.; van der Ploeg, G. E.; Withers, R. T. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: Based on persistent reports of low oxygen consumption VO(2) from Medical Graphics CPX/D metabolic carts, we compared the CPX/D against an automated Douglas bag system. METHODS: Twelve male athletes completed three, randomized 25-min bouts (5 min at 100, 150, 200, 250, and 300 W) on a cycle ergometer with intervening 30-min rests. One bout was measured on each of the CPX/D, the CPX/D with altered software (CPX/DDelta), and an automated Douglas bag system at Flinders University (FU). The CPX/DDelta software alteration was an apparent lag time correction factor of 60 ms. RESULTS: For the CPX/D, both VO(2) and VCO(2) were significantly lower than the FU system at 100-300 W, and the relative differences ranged -10.7 to -12.0% and -7.7 to -8.2%, respectively. Altering the software approximately halved the VO(2) discrepancy between the CPX/DDelta and FU systems. When data from all five workloads were pooled, V(E) of the CPX/D (67.2 +/- 26.4 L x min-1) and CPX/DDelta (67.5 +/- 26.9 L x min-1) were significantly lower than for the FU system (70.5 +/- 27.1 L x min-1); and at 300 W, the relative differences were -4.0% and -3.4% for the CPX/D and CPX/DDelta, respectively. Altering the software changed the pooled %O(2) from 16.24 +/- 0.40% for the CPX/D to 16.04 +/- 0.39% for the CPX/DDelta, and these were significantly different than pooled data for the FU system (16.15 +/- 0.39%).CONCLUSIONS: During submaximal exercise, the CPX/D yields VO(2) values that are approximately 11% lower than the criterion system, and the source of the discrepancy does not appear to be primarily related to volume measurement. A disturbing observation is that factory defaults for the lag time use different correction factors, which vary by 60 ms and this significantly alters VO(2) and VCO(2).